g/Głusi w bibliotece = The Deaf in the library - Korytkowska, Marta; Przastek-Samokowa Maria (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
Deaf people are a specific group of readers. The literature on the subject pays special attention to the problems of the Deaf, especially deaf people in pre-lingual and peri-lingual life, connected with the acquisition and learning of the Polish language, which sometimes constitutes a foreign language for them. Many deaf people do not use libraries because they feel insecure on account of the communication barriers they encounter. In addition, librarians do not fulfill the special needs of deaf people, often treating them as ordinary users. Deaf people themselves do not always consider themselves disabled, but want to be treated as a separate social group - the Deaf as a linguistic and cultural minority. In the article, attention is drawn to the existence of this minority, togethe rwith their reading needs, problems and barriers related to reading and traditional books in Polish as well as the specificity of working with the deaf reader and ways of encouraging deaf people to use libraries. The subject of alternative forms for a traditional book in Polish is also discussed: Sign Writing - methods of recording sign language, together with books on video translated into sign language, special books for children using sign language, and books that are easy to read.
Keywords: osoby niesłyszące; biblioteka; bariery komunikacyjne; Język migowy; czytelnictwo; Deaf people); library; communication barriers; Sign language; reading